ANALISIS PENYERAPAN TENAGA KERJA PLTU DAN KONDISI SOSIAL EKONOMI TENAGA KERJA DI DESA TANJUNG TIRAM KECAMATAN MORAMO UTARA KABUPATEN KONAWE SELATAN - Erik Sideni; Sabir Ahmad; Muhammad Armawaddin (JEP (Jurnal Ekonomi Pembangunan), 2021)
This study aims to analyze the absorption of PLTU's workforce and the socio-economic conditions of labor in Tanjung Tiram Village. The analytical method used is qualitative by describing the data descriptively. The technique of collecting data was carried out by observation, interviews, and documentation. The results of this study indicate that only 32 people are employed in the PLTU construction project .The level of income received by the community that has been absorbed in the PLTU is in the high category because it can pay for children's education up to tertiary education and can meet their daily life. Besides that, the health conditions of the people / employees are all healthy, because the PLTU provides free medical treatment to people who are absorbed in working at the PLTU. Furthermore, the condition of the houses that have been absorbed has undergone many changes, almost all the houses of the people who work in the PLTU are included in the permanent category.